PENERAPAN PENGAJARAN DENGAN METODE ROLE PLAYING MINI DRAMA UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN SEJARAH DALAM MATERI PROKLAMATOR DAN PERAN PROKLAMATOR DI KELAS XI IPS DI SMA NEGERI 1 TEBING SYAHBANDAR TAHUN PELAJARAN 2022 / 2023 - NAINGGOLAN, RUSMAYANTI (JURNAL ILMIAH MAKSITEK, 2023)
One of the innovative learning models that can be done by Smart Teachers in the classroom is to apply the role playing learning model. The definition of role playing learning is a learning method in which learners directly act out a problem that focuses on issues about human relationships. learners are given the opportunity to describe or express a character being played and other learners are tasked with observing the course of the drama. In certain parts, for example in the middle, the teacher can stop the drama and give students the opportunity to express opinions and criticism about the learning material being studied. The purpose of this study is to determine the level of students' ability to learn history before using the mini drama role playing learning model and afterwards. role playing model is a learning model by assigning students to play a character in the material or event expressed in the form of a simple story that has been designed by the teacher. In this study only involved one class that received learning treatment using the role playing method through mini drama. The approach that researchers use in this study is a qualitative and quantitative approach. this approach through two results, the first is called pre-action cycle I or assessment before using the mini drama role playing model and the second is called cycle II or after using the mini drama role playing model. The learning outcomes of students in cycle I increased was 41.66%, and increased in cycle II to 82.35%.